Variables relating to a child's attitude and expectancies towards alcohol drinking - Cayabyab, Ebony A.
This study investigated whether parent-relationship perceived parent alcohol drinking attitudes, peer relationship, and perceived peer attitude towards alcohol drinking significantly related to the child's attitude and expectancy towards alcohol drinking. One hundred twenty-one (121) first to fourth year students of Miag-ao National High School completed a series of questionnaires designed to measure the variables under investigation. The design was correlational in nature, thus, the Pearson r correlation coefficient was used to analyze the data. Results showed that both the respondent's attitude and expectancies towards alcohol drinking are significantly related to both their perceived parent's and peers' attitude towards drinking. However both the respondent's attachment to parents and peers did not show such significant relationship with their attitude and expectancies towards alcohol drinking.